THE IMPLEMENTATION OF PROCESS APPROACH IN PARAGRAPH WRITING FOR STUDENT IN UNIVERSITY - Uji Nur Hidayati (MIYAH : Jurnal Studi Islam, 2017)
Abstract: Writing plays an important role for English Foreign Language (EFL) in the real language teaching. This study is a qualitative study and presenting descriptively the data of condition that existed at the time. The subjects of the study are the lecturer in Writing I and the students of Writing I at STKIP PGRI Nganjuk. This qualitative research is conducted to investigate the implementation of Process Approach has been implemented, which involves the description, recording, and interpretation of condition that existed at that time. The sources of data of this study are verbal and non-verbal behaviors of the lecturer and the studentsâ€™ transcription in teaching and learning. There are some findings obtain from this study. The first finding is the steps of process approach are conducted sequent but the lecturer did not adjust the steps with the needs of syllabus. As a result, the lecturer only implements one step of planning in process approach namely listing technique. Thus, the implementation of process approach is small extent. The second finding shows that most of students respond well because they argue hat process approach is easy to be implemented. The last finding shows that studentsâ€™ ability is moderate because the most of studentsâ€™ scores in Writing I course is dominated by â€œBâ€ score.Key Words: Process Approach, Paragraph Writing